Carbon capture and utilization for carburization of hydrogen DRI: A techno-economical system analysis of possible synergies for future mine-to-iron plants at LKAB - Andreasson, Jakob; Emme, Carl (My University, 2021)
This thesis investigates the technical and economic viability of capturing CO2 from LKAB’s pelletizing plants and utilizing the CO2 as a carbon source for carburization of hydrogen reduced direct reduced iron (DRI). The CO2 is captured through a post combustion carbon capture process utilizing an amine solvent. The thesis suggests two routes for CO2 utilization where CO2 is converted to CO or methane, which can carburize DRI, and additionally a CO2 permanent storage route where DRI is instead carburized with bio-methane. The work includes: mass and energy balances of each pelletizing plant to determine magnitudes of carbon and produced DRI, modelling of the carbon capture plant to validate technical viability of capturing from the low CO2 concentrations found in LKAB’s flue gases, and an economic assessment to compare the different routes. The mass and energy balance shows that the CO2 in the flue gases is sufficient to be of interest for the DRI carburization. For stand-alone application to LKAB’s plants, i.e no integration between plants, the level of carburization possible using only CO2 from pelletization are between 0.45-1.2wt% carbon content of the DRI. The CO2 modelling concluded that it’s feasible to capture CO2 from LKAB’s flue gases data at similar costs as for other industrial sites, due to the presence of available excess heat. The cost assessment showed that the CO-route has a similar cost to a reference case without CO2 capture and where carburization occurs with biomethane. The methane and storage route were more expensive. A sensitivity analysis revealed that the cost results are highly sensitive to the price of electricity and solid biomass. This thesis has shown technical and economical feasibility for LKAB to implement CO2 capture and/or utilization at scale together with the manufacturing of hydrogen DRI. Carburization of DRI with CO2 may be competitive to carburization with biomethane depending on the development of the energy system. If emissions from the pelletizing plant are reduced with other solutions, CO2 can be captured from other industries in the geographical proximity to LKAB’s operations. The carburization of DRI has the potential to be a carbon sink if the CO2 comes from biomass combustion.
Keywords: Carbon capture; CCU; CCUS; DRI; Carburization; Pelletizing